1995
DOI: 10.1007/bf00207271
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid surface density determines the partitioning and permeability of acetic acid in DMPC:cholesterol bilayers

Abstract: Relationships between the permeability coefficient (PHA) and partition coefficient (K m/w) of acetic acid and the surface density of DMPC:cholesterol bilayers have been investigated. Permeability coefficients were measured in large unilamellar vesicles by NMR line broadening. Bilayer surface density, sigma, was varied over a range of 0.5-0.9 by changing cholesterol concentration and temperature. The temperature dependence of PHA for acetic acid exhibits Arrhenius behavior with an average apparent activation en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
92
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 48 publications
11
92
0
Order By: Relevance
“…The reduction of the leak conductance of asolectin membranes induced by cholesterol is consistent with findings that cholesterol greatly reduces the permeability of lipid membranes to different substances (19)(20)(21)(22), which is generally attributed to the ability of cholesterol to promote order in lipid chains. However, we observed that cholesterol incorporation into asolectin membranes essentially eliminated the PA-induced increase in proton selectivity observed in pure asolectin membranes.…”
Section: Membranes Modified By Fa In the Bathsupporting
confidence: 87%
“…The reduction of the leak conductance of asolectin membranes induced by cholesterol is consistent with findings that cholesterol greatly reduces the permeability of lipid membranes to different substances (19)(20)(21)(22), which is generally attributed to the ability of cholesterol to promote order in lipid chains. However, we observed that cholesterol incorporation into asolectin membranes essentially eliminated the PA-induced increase in proton selectivity observed in pure asolectin membranes.…”
Section: Membranes Modified By Fa In the Bathsupporting
confidence: 87%
“…Experimental data on the free energy difference between the headgroup region and the water phase have been obtained for acetic acid; from the partition coefficient in DMPC vesicles, a value ∆G ≈ -0.45 kJ/mol was calculated. 53 This negative value is in qualitative agreement with our AL-CG results, whereas it is inconsistent with the AL results, which gave a positive free energy difference. 34 However, there is a discrepancy of a factor of ∼5 between that experimental value 53 and our AL-CG result.…”
Section: Resultssupporting
confidence: 56%
“…The difference in behavior that we observe compared with others, both in trend and magnitude, is clear and we briefly consider the reasons below. We note, however, that the trend is not entirely without precedent; the gel-phase dipalmitolyphosphatidylcholine (DPPC) studies of Xiang and Anderson (14,16,17) also found a decreasing permeation coefficient from acetic to propionic acid, but for larger acids P increased again (17). DPPC is a fully saturated lipid, thus P values are orders of magnitude smaller in the gel phase (17) and so are easier to measure accurately.…”
Section: Resultsmentioning
confidence: 78%
“…On the other hand, some weak acid protonophores may also exert detrimental effects on cellular processes such as oxidative phosphorylation, apoptosis (7), and photosynthesis (8). The transport of weak acids across model cell membranes and the determination of permeation rates have consequently been the subject of a considerable number of studies (9)(10)(11)(12)(13)(14)(15)(16)(17)). …”
mentioning
confidence: 99%
See 1 more Smart Citation